Improving Correctional Classification, New York, 1981-1983 - Wright, Kevin ([Verlag nicht ermittelbar], 1985)
There were three specific goals of this research. The first was to evaluate three procedures currently available for the classification of correctional inmates: the Risk Analysis method, Megargee's Minnesota Multiphasic Personality Inventory Typology, and Toch's Prison Preference Inventory. Second, the research devised and tested a postdictive model of adjustment to prison life. Third, a new classification scheme was developed for predicting inmate adjustment to prison life that considers individual and organizational (contextual) factors and various interactions between the two. These data were collected from a sample of 942 volunteer inmates from ten New York state correctional facilities, five of which were maximum security and five of which were medium security facilities. Only one-half of the original 942 inmates completed the MMPI. Background and questionnaire data were collected during the summer and fall of 1983. Outcome data on each inmate infraction were collected for a three-year period prior to that time. Each case in Part 1, Merged Survey Response File [PPQ, PEI, PAQ], represents survey response data from an individual inmate, with variables from the Prison Preference Questionnaire (PPQ), the Prison Environment Inventory (PEI), and the Prison Adjustment Questionnaire (PAQ). Cases in Part 2, Medical Records, are records of medical contacts and diagnoses of inmates' illnesses. Part 3, Minnesota Multiphasic Personality Inventory, contains personality assessment information and scores for each individual offender. Data in Part 4, Sample Data [Background Characteristics], consist of individual-based variables covering inmates' background characteristics. Part 5, Offenses and Disciplinary Action Records, contains records of offenses and disciplinary action by individual offender. The client number is unique and consistent across all data files.